Oscillation transmission and volume delivery during face mask‐delivered HFOV in infants: Bench and in vivo study. Issue 7 (25th February 2016) - De Luca, Daniele; Costa, Roberta; Visconti, Federico; Piastra, Marco; Conti, Giorgio
Summary: Objective: Noninvasive high frequency oscillatory ventilation (NHFOV) has not been studied beyond neonatal age and with interfaces other than nasal prongs. We set up a preliminary study to investigate feasibility, oscillation transmission, and volume delivery of face mask‐delivered NHFOV in a bench model mimicking a normal 1‐year infant without any lung disease and then in vivo in a series of infants with same characteristics. Design: A mannequin with upper airways was connected to an electronic active lung simulator ventilated through NHFOV with varying parameters. Volume delivered by oscillations (oTv), oscillatory pressure ratio, and estimation of ventilation (DCO2) were measured at the lung simulator. Four infants were ventilated with face mask‐delivered NHFOV for 2 hr and monitored with respiratory inductance plethismography. Vital parameters, oscillatory pressure ratio, oscillatory (RIPo), and spontaneous cage/abdomen displacement (RIPs) were recorded. Results: There was a dampening of oscillation amplitude both on the bench model and in vivo: oscillatory pressure ratios at the mask were 80% and 17%, respectively. Significant correlations exist between oscillatory pressure ratio (only when this latter was <0.038) and oTv (r = 0.48; P  < 0.001) or DCO2 (r = 0.47; P  < 0.001). At multivariate analysis, oscillatory pressure ratio was a main determinant of oTv and DCO2. Oscillations were slightly visible on the chest in vivo and RIPo was about 5% of RIPs. NHFOV did not change vital parameters and did not cause discomfort. Conclusions: Face mask‐delivered NHFOV is feasible in a model of 1‐year infant. No major complications occurred in vivo. Oscillations are superimposed to the spontaneous breathing and are significantly dampened. Pediatr Pulmonol.Pediatr Pulmonol. 2016;51:705–712 . © 2016 Wiley Periodicals, Inc.